Comparison of the short-chain fatty acids in normal rat faeces after the treatment of Euphorbia kansui, a traditional Chinese medicine for edoema - Dongjing Jiang; Sijia Guo; An Kang; Yonghui Ju; Jingxian Li; Sheng Yu; Beihua Bao; Yudan Cao; Yuping Tang; Li Zhang; Weifeng Yao (Taylor & Francis Group, 2020)
Context As a toxic traditional Chinese medicine for edoema, Euphorbia kansui S.L. Liou ex S.B. Ho (Euphorbiaceae) (EK) stir-fried with vinegar for detoxification was associated with alterations of gut microbiota. However, the evidence of correlation between short-chain fatty acids (SCFAs) and toxicity of EK has not been confirmed. Objective In order to study the biological basis of detoxification of EK stir-fried with vinegar (VEK), a rapid, sensitive and validated GC-MS method was developed to determine SCFAs in normal rat faeces after given EK and VEK. Materials and methods Sprague Dawley rats were orally administered 0.5% CMC-Na (control group), EK (EK-treated group) and VEK powder (VEK-treated group) at 680 mg/kg for six consecutive days (eight rats each group). Fresh faeces samples were promptly collected, derivatized and then analyzed by GC-MS. Results The ranges of LOD and LOQ were within 0.13-1.79 and 0.45-5.95 μg/mL, respectively. The RSD values of intra-day and inter-day precisions were less than 15%. Four SCFAs were generally stable under four storage conditions. The extraction recoveries were ranged from 53.5% to 97.3% with RSD values lower than 15%. The concentrations of four SCFAs in EK and VEK were decreased significantly compared with those not administered (EK-treated, p < 0.01; VEK-treated, p < 0.05 and p < 0.01). After being stir-fried with vinegar, the concentrations were all increased (p < 0.05 and p < 0.01). Discussion and conclusions The negative correlation between SCFAs and toxicity of EK may provide evidence for biological mechanism and toxic Chinese medicine.